An exploration of gastropod-borne parasites with a focus on intestinal schistosomiasis in Biomphalaria snails inhabiting the Great African Lakes - Andrus, Peter S. (2023)
Gastropod-borne parasitic diseases are a significant concern for public health all over the world, but particularly in developing countries. Many species of terrestrial and freshwater gastropods serve as the intermediate host for various parasites with medical and/or veterinary significance. One such example is the intravascular trematode species, Schistosoma mansoni (Digenea: Schistosomatidae), which is the leading cause of intestinal schistosomiasis globally. The obligatory intermediate host of S. mansoni is the freshwater snail genus, Biomphalaria (Gastropoda: Planorbidae). The vast majority of intestinal schistosomiasis cases occur in sub-Saharan regions of Africa, with countries in East Africa suffering from a high prevalence of S. mansoni in and around the Great African Lakes. The hyper-endemic nature of intestinal schistosomiasis at Lake Albert and Lake Victoria is a significant public health concern.